Friendly Governance: Assessing Sociopolitical Factors in Allegations of Corruption. (4th March 2019) - Russell, Chris
Abstract : This qualitative-interpretive case study centers on allegations of corruption concerning Utah's former Attorney General, John Swallow, who resigned from office in December 2013. It addresses how sociopolitical influences affect the motivations and behavior of public officials. Semistructured interviews and archival research comprise the methods utilized. Behavioral ethics serves as a lens to assess the case study findings. This article finds that relationships encourage trust and loyalty between the public official and his/her social network, often distorting judgment and leading to unethical behavior. It further argues that a particular ideology enabled, and compensated for, a lack of commitment to virtuous behavior in office. This article contributes to the literature by providing a fuller understanding of the nature of legal corruption. Furthermore, it emphasizes the importance of culture and its role in contributing to such corruption.